ResearchGate: An effective altmetric indicator for active researchers?. (February 2016) - Yu, Min-Chun; Wu, Yen-Chun Jim; Alhalabi, Wadee; Kao, Hao-Yun; Wu, Wen-Hsiung
Abstract: As research performance becomes increasingly important for academic institutions in competition for rankings, student recruitment, and funding, many performance indicators have been developed to measure various aspects of research performance. ResearchGate combines bibliometrics and altmetrics to create a more comprehensive performance measure for researchers and institutions. The ResearchGate score, the flagship indicator calculated by an undisclosed algorithm, is a metric that measure scientific reputation. In this research, ResearchGate metrics are firstly compared with those that Research Excellence Framework (REF) and Quacquarelli Symonds (QS) World University Rankings to assess the quality of UK universities and global universities respectively. This study then utilizes correlation analysis to examine whether ResearchGate metrics demonstrate effectiveness on the researcher level in comparison with SciVal metrics. For this research, 300 ResearchGate members from the supply chain management field were selected. The results provide empirical evidence that demonstrate that the ResearchGate score can be an effective indicator for measuring individual researcher performance. Highlights: We study the effectiveness of ResearchGate score at the researcher level. We use correlation analysis to compare ResearchGate score and FWCI of SciVal. ResearchGate members in the discipline of supply chain management are sampled. Our results suggest RG score is an effective indicator at the individual level.